The Correlation between Students’ Habit of Listening English Songs on Spotify and their Vocabulary Mastery - Febriani, Feby; Addinna, Ainul (Universitas Negeri Padang, 2025)
Vocabulary mastery plays a crucial role in English language proficiency, yet many students still face challenges in acquiring and using new vocabulary effectively. With the increasing use of digital platforms, Spotify has become a familiar application for listening to English songs, offering potential as a learning medium. The purpose of this study is to investigate the correlation between students’ Spotify English songs listening habit and mastery of vocabulary at 2023 academic year of English educational study program at UNP. This research employed a quantitative with correlational design. The researcher was use questionnaire and Vocabulary Test Level (VLT) as the instruments of this research. The participants of this research were 37 students which were chosen using purposive sampling. The result findings indicated that the average level of listening habit was high (M = 80.97) and vocabulary mastery was categorized as very good (M = 81.86). However, the Pearson Product Moment correlation analysis indicated a weak and statically non-significant negative correlation (r = -0.220, p > 0.05) between the variable X and variable Y. In conclusion, this research found there is no significant correlation between students’ Spotify English songs listening habit and mastery of vocabulary.